Strategies for the development of international sport diplomacy in the volleyball federation of the Islamic Republic of Iran - Fallah Nassiri , Reza Mir; Monazami , Amir Hosein; Aghaei, Najaf; Rahimizadeh, Meysam (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
In recent years, Iran’s volleyball sport has made significant progress and the Iranian national team has been able to compete in the World Volleyball League. This situation has provided the Iranian Volleyball Federation with diplomatic opportunities. The purpose of this study was to develop strategies for the development of international sport diplomacy in the volleyball federation of the Islamic Republic of Iran. This study was conducted qualitatively by interviewing Iranian volleyball officials (N = 4), academic experts in sport diplomacy (N = 4) and internationally experienced coaches and referees (N = 5). Data analysis with theme analysis techniques revealed that the five emerging themes included: challenges, principles of effective international sport diplomacy, international sport diplomacy success factors, international diplomacy development strategies in volleyball federation, and the implications of international sport diplomacy, including 18 sub-themes and 43 open codes. All these aspects are analyzed and discussed in the present study.